Efficacy of Lower Extremity Mirror Therapy on Balance in Children With Hemiplegic Cerebral Palsy: A Randomized Controlled Trial - zaid, Nehad A. Abo; Zaghloul, Hebatallah M.; Khalifa, Heba A. .; E. Ali, Mohammed; Abdelsamee, Mohammed Y. (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To assess the efficacy of lower extremity mirror therapy on balance in children with hemiplegic cerebral palsy. Methodology: Sixty hemiplegic cerebral palsy children were selected in this study after the assessment of eligibility. Their ages ranged from eight to twelve years. They were randomly assigned into two equal groups. The control group (GA) received a guideline protocol. And study group (GB) received the same guideline protocol in addition to mirror therapy three times / weak for three successive months. Assessment of balance by Biodex balance system pre and post-treatment that continued three months. Results: Post-treatment, significant improvement was in the Overall stability index, the Anteroposterior stability index, and the Mediolateral stability index in both groups and in favor of (GB) (P< 0.05). Conclusions: Lower extremity mirror therapy has a significant effect on balance in children with hemiplegic cerebral palsy.